Simulations of Non-Equilibrium and Equilibrium Segregation in Nickel-Based Superalloy Using Modified Scheil-Gulliver and Phase-Field Methods - Okugawa, Masayuki; Izumikawa, Daichi; Koizumi, Yuichiro (MATERIALS TRANSACTIONS, 2020)
Solute segregation significantly affects material properties and is an essential issue in the additive manufacturing (AM) process. In the present study, we have investigated (i) non-equilibrium segregation in solidification, and (ii) equilibrium segregation at grain boundary in Ni-based Hastelloy-X (HX) superalloy using the modified Scheil-Gulliver model (i.e., Scheil-Gulliver model with back diffusion) and a phase-field model. We have found that the concentrations of all solute elements on grain boundary differ from those in face-centered cubic (FCC) phase matrix even in equilibrium state. In the non-equilibrium segregation, the segregations of Mo, Cr, and Mn and the depletion of Fe become more remarkable than the equilibrium segregation. Moreover, we have investigated the segregation in HX-based alloys with different Fe concentrations to propose a guide for tailoring the chemical composition of HX via the control of the segregation behaviors. The equilibrium-segregation simulation revealed that the Cr segregation in the grain boundary phase increased with the increase of Fe concentration. This result suggests that by controlling the Fe concentration, the Cr concentrations on grain boundaries can be controlled without changing directly the Cr concentrations. This finding opens new way of controlling materials properties which are dominated by the nature of grain boundaries such as corrosion resistance, crack sensitivity, high temperature strength.